Association between genomic features and toxic metal(loid) accumulation in left-sided and right-sided colorectal cancer - Yu, Shoujiang; Fu, Min; Wang, Yurong; Lin, Ling; Ji, Shushen; Du, Feng; Song, Li; Wang, Mengzhu; Zhai, Yufeng; Zhao, Jiangman; Huang, Min (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a high heterogenous disease of genetic variations, which was influenced by tumor anatomic location and toxic metal(loid) accumulation. Current study aims to investigate genomic heterogeneity of CRC influenced by toxic metal(loid) accumulation based on tumor anatomic location.MethodsIn this study, a total of 94 patients with CRC were recruited including 69 left-sided tumors and 35-right sided tumors. The genomic mutation landscape and microsatellite instability (MSI) of tumors were analyzed. The blood metal(loid) element levels were tested by inductively coupled plasma emission spectrometry (ICP-MS).ResultsA total of 642 somatic variations across 24 genes were identified in 94 CRC patients. The most frequently mutated genes were TP53 (n=83%), followed by APC (n=67%), KRAS (52%), EGFR (41%) and PIK3CA (33%). The mutated frequency of TP53 (88.4% vs 68.0%, P=0.02) and APC (75.4% vs 44.0%, P=0.004) in left-sided tumors were significantly higher than that of right-sided tumors. Blood Hg concentration was significantly and positively correlated with numbers of variations per tumor sample (r=0.237, P=0.021). Blood As (r= -0.207, P=0.046), Sr (r= -0.256, P=0.013) and Ba (r= -0.274, P=0.08) level of patients with MSS tumor was significantly higher than that of patients with MSI tumor. Cd level of patients with tumor in left side was significantly lower than that in right side (P=0.028).ConclusionsThis study presented the comprehensive genomic landscape of 94 CRC patients according to tumor anatomic location. The blood toxic metal(loid) accumulation may have potential influence on genomic features.